The Ottoman Road to War in 1914 : The Ottoman Empire and the First World War - Aksakal, Mustafa (Cambridge, UK Cambridge University Press, 2008)
"Why did the Ottoman Empire enter the First World War in late October 1914, months after the war's devastations had become clear? Were its leaders "simple minded," "below-average" individuals, as the doyen of Turkish diplomatic history has argued? Or, as others have claimed, did the Ottomans enter the war because War Minister Enver Pasha, dictating Ottoman decisions, was in thrall to the Germans and to his own.
Includes Index and Bibliography
Keywords: Turkey -- History -- Mehmed V, 1909-1918 -- World War, 1914-1918 -- Turkey